SURAT PERINTAH KERJA KARYAWAN RIGLESS PADA PT. PRAKARSA PRAMANDITA BERBASIS WEB - Cindy Dea Vella; Erliza Yubarda; Miftahul Jannah; Candra Surya (JSR : Jaringan Sistem Informasi Robotik, 2022)
The process of requesting a work order for rigless employees at PT. Pramandita's initiative is still being carried out manually. Previously, employees who were at the work location and had received orders for additional work had to go to the office first to request and administer the SPK (Work Order). In addition, the absence of a report recapitulation of making SPK causes leaders to experience difficulties because data is often lost. So the author feels the need to design a web-based application to facilitate the activity of requesting a work order and recapitulation of reports. The process of designing this Web-based application uses the Unified Modeling Language (UML) programming language, where the system design consists of a detailed design of output, input, and files that aim to support the application creation process.Keywords: Work order Application, PT. Prakarsa Pramandita.